2011
DOI: 10.1563/aaid-joi-d-09-00084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoride on the Corrosion Behavior of Ti and Ti6Al4V Dental Implants Coupled With Different Superstructures

Abstract: The effect of fluoride ion concentration on the corrosion behavior of Ti and Ti6Al4V implant alloys, when coupled with either metal/ceramic or all-ceramic superstructure, was examined by different electrochemical methods in artificial saliva solutions. It was concluded that increased fluoride concentration leads to a decrease in the corrosion resistance of all tested couples. The type of the superstructure also showed a significant effect on the corrosion resistance of the couple.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Fluoride modification on the implant surface leads to morphologic and physiochemical phenomena that are of significance for osteoblastic differentiation and interfacial bone response (Cooper et al, ; Ellingsen, ; Ellingsen, Johansson, Wennerberg, & Holmén, ). Unlike those fluorine elements embedded into fluoride‐modified titanium implants in the form of stable compounds, the free serum fluorine around the titanium implants under fluoride exposure affects the surrounding bone metabolism and reduces the corrosion resistance of titanium (Anwar, Kheiralla, & Tammam, ). Joska and Fojt () found that the excessive free fluoride could exist in the whole depth of oxide layer on titanium surface, with an increased thickness but less protective than that formed in fluoride‐free solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride modification on the implant surface leads to morphologic and physiochemical phenomena that are of significance for osteoblastic differentiation and interfacial bone response (Cooper et al, ; Ellingsen, ; Ellingsen, Johansson, Wennerberg, & Holmén, ). Unlike those fluorine elements embedded into fluoride‐modified titanium implants in the form of stable compounds, the free serum fluorine around the titanium implants under fluoride exposure affects the surrounding bone metabolism and reduces the corrosion resistance of titanium (Anwar, Kheiralla, & Tammam, ). Joska and Fojt () found that the excessive free fluoride could exist in the whole depth of oxide layer on titanium surface, with an increased thickness but less protective than that formed in fluoride‐free solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse electrochemical methods were used to observe the effect of fluoride ion concentration on the corrosion behavior of Ti and Ti6-Al-4V implant alloys, in AS when coupled with either metal/ceramic or all ceramic superstructures. This lead to the conclusions that while fluoride concentration increases corrosion resistance of Ti and its Ti6-A1-4V alloy decreases [12]. Ti-Co alloy [10] and Ti-Cu alloy [24] gave parallel consequences.…”
Section: Effects Of Fluoride Ion On Corrosion Resistance Of Dental Almentioning
confidence: 99%
“…To recognize these effects, numerous investigations were undertaken. Corrosion resistance of metals and alloys in AS, in the presence of fluoride has been investigated [1,10,11,12,14,19,24] The presence of fluoride ions (added as NaF) drastically affects the corrosion behavior of Ti metal, Ti-6Al-7Nb, and Ti-6Al-4V alloys and constituent metals in AS as confirmed by electrochemical methods [1]. All the titanium alloys in fluoridated acidified saliva show an active behavior due to the presence of major concentrations of HF and HF2− species that dissolve the spontaneous air-formed oxide film giving rise to surface activation [13].…”
Section: Effects Of Fluoride Ion On Corrosion Resistance Of Dental Almentioning
confidence: 99%
See 1 more Smart Citation
“…Titania (TiO 2 ) has been previously shown to have good biocompatibility with human corneal stroma fibroblasts and epithelial cells 1415 In addition TiO 2 has a protective layer of oxide film that is stable, bioinert and provides the material with resistance to corrosion in tissue fluids for example, artificial saliva 1617 These properties make TiO 2 a potential substitute to HA as a synthetic OOKP skirt material.…”
Section: Introductionmentioning
confidence: 99%